Tampil Percaya Diri Pada Saat Presentasi Tugas Akhir atau Sidang Skripsi - Kurniasih, Nuning (Forum Kerjasama Pendidikan Tinggi, 2023)
The final project exam or defend theses often causes anxiety for some students. Anxiety is a normal response to situations that will be faced. However, excessive anxiety will affect the lack of confidence at the time of the thesis defense. In addition to anxiety, student obstacles in presenting the final project / thesis include lack of practice and lack of mastery of presentation techniques. This service activity is intended to provide an overview to the target audience in preparing themselves to appear confident during the final project presentation or thesis defense. This community service activity is delivered through training to undergraduate students in the Nutrition and Feed Technology Study Program at Bogor Agricultural University who are taking Scientific Writing and Presentation Courses as many as 150 people. To provide a comprehensive understanding of the problems during the final project / thesis examination, I compiled three material frameworks which included an understanding of the final project, the final project/ thesis examination process and how to build confidence for the final project presentation or defend thesis. There are three things that candidates need to prepare in order to appear confident when delivering a final project presentation or thesis examination, namely physical readiness, mental readiness and presentation strategies and techniques. To determine the target audience's understanding of the material presented, I gave the opportunity to several students to present their thesis plans and asked them some questions. From the answers of the target audience, it can be seen the ability to analyze, skills in delivering thesis plan, answering questions and defending arguments. These are the skills needed in facing the final thesis examination.